Interlay versus underlay type 1 tympanoplasty: a comparative study of the techniques in 100 cases - Sharma, Nitin; Sharma, Pritosh; Goyal, V. P.; Sharma, Kumar Gaurav (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2018)
Background: Type 1 tympanoplasty is a surgical technique used to restore the integrity of tympanic membrane as well as to improve hearing level in patients with large central perforations (inactive mucosal chronic otitis media). Methods: This is a randomized prospective study of 12 month duration from January 2017 to December 2017 in 100 patients of chronic otitis media inactive mucosal type with large central perforation admitted in the E.N.T department at Geetanjali Medical College and Hospital, Udaipur. Results: The graft uptake rate in the present study was found to be 96% and 90% respectively in interlay and underlay techniques. Post operatively after 12 weeks mean air bone gap was maximum reduced in Interlay tympanoplasty. Conclusions: The present study showed that Interlay technique had a better graft take rate as well as hearing improvement in large central perforation of chronic otitis media than the underlay technique.